When the Eyes of the World Were on La Côte-Nord: The Adventures of a Paramount Newsreel Cameraman in Québec - Fernstrom, Ray (Nouvelles vues, 2020)
In this first-person account, the Swedish-born cameraman Ray Fernstrom recalls his crossing of Quebec in an aeroplane piloted by aviation pioneer Roméo Vachon in 1928. Fernstrom, who was then employed by the Paramount News newsreel, was on a mission to get images of the crew members of the Bremen, who had crash-landed on Greenly Island, Quebec, on April 13, 1928, after completing the first transatlantic flight from East to West.